Efeito do pré-condicionamento isquêmico remoto no transplante ortotópico de fígado de doadores em parada cardíaca. Estudo experimental em suínos - Morais, Lúcio Kenny (2012)
Introduction: Improved liver function from non-heart-beating donors seems to be related to short periods of warm ischemia; hence ischemia-reperfusion injury is a critical unsolved issue. Remote Ischemic preconditioning (PC) has been shown to protect the liver from ischemia-reperfusion injury. However little is known about the usefulness of ischemic precondition as a strategy to improve tolerance of non-heart-beating liver grafts to warm ischemia. Therefore we designed an experimental study aiming the effects of ischemic preconditioning on liver transplantation from non-heart-beating donors. Methods: Protocol was approved by Federal University of Goias Ethics Committee. Twentyfour Landrace pigs were assigned into 4 groups: I: after cardiac arrest livers were procured and transplanted; II: after PC and cardiac arrest livers were procured and transplanted; III: after PC and cardiac arrest, a 15 minutes period of warm ischemia was observed before livers were procured and transplanted; IV: after PC and cardiac arrest, a 30 minutes period of warm ischemia was observed before livers were procured and transplanted. Donors: cardiac arrest was obtained by ligation of coronary arteries and interruption of ventilation. PC (10` x 10`) and warm ischemia waiting time were observed accordingly. Livers were flushed with 4°C HTK solution cooled and procured. Recipients: standard technique was used. After one hour of reperfusion, blood and liver samples were collected and euthanasia was carried out. Non-parametrical statistical tests were applied. Results were expressed as medians. A value of p<0.05 was considered statistically significant. Results: AST, ALT, lactic acid and factor V levels were similar for the different studied groups by the end of one hour of reperfusion. A trend towards a deteriorated liver function was observed in group IV. When histological variables were addressed, vacuolization of hepatocytes and cell dropout scores were similar in all groups. Congestion score, vacuolization of hepatocytes and cell dropout scores tended to be higher in animals from group IV, but with no statistical significance. Conclusions: Remote ischemic preconditioning showed no benefits to liver grafts from nonheart- beating donors. Even though it did not result in benefits, no prejudice could be noticed in this research, as well.